Rancang Bangun Sistem Informasi Pelayanan Kesehatan Berbasis Customer Relationship Management Menggunakan Teknologi Short Message Service (SMS) - Sutrisno, Trismianto Asmo Sutrisno; Prahasto, Toni; Suhartono, Suhartono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
Recently, there are many hospitals as the health-care services choose to use the concept of Customer Relationship Management (CRM) to build the trust bridges between the hospitals and their patients. The implementation of CRM in health caring, especially for pregnant women needs to do; such as the delivery of information related to the pregnant women to get antenatal care as the scheduled or pregnant women desire to obtain information dealing with their pregnancy. The irrelevant, slow and inaccurate information can cause the health care services given to the patients are not optimal, so that they can reduce patientsâ€™ loyalty toward the health-care services. This research resulted health care information system based on Customer Relationship Management using Short Message Service (SMS) technology with case study of health care for pregnant women. The resulted information system is produced by the System Development Life Cycle methodology using the Waterfall model. One of the features produced is the pregnant women will receive a confirmation SMS to obtain antenatal care with a schedule until 28 weeks of their pregnancy check up every four weeks, 28-36 weeks of their pregnancy check up every two weeks, and 36-40 weeks of their pregnancy check up once a week. Â  Keywords: Pregnant Women, Antenatal Care, Customer Relationship Management, Short Message Service